Computer-assisted sperm analysis (CASA) in veterinary science: A review - SINGH, A K; KUMAR, A; BISLA, A (The Indian Journal of Animal Sciences, 2021)
Computer-assisted sperm analysis (CASA) allows an assessment of sperm motion and morphology more accurately and objectively than by subjective evaluation. Although, CASA instruments have improved significantly during last 40 years especially in terms of software, image capture and computer settings, little has changed regarding processes for analyzing sperm motion attributes. The main problem is related to validation, consistency and optimization of equipment and procedures. Differences among CASA systems denote problems of objective analysis of results between different semen processing units. If validated, CASA systems can provide a great tool to objectively compare sperm motility and morphology. Sperm motility is one of the indicators most evaluated before and after cryopreservation vis-à-vis quality and fertilizing ability. Researchers have determined a possible relationship of CASA outputs with bull fertility in vivo; however, a clear association has not yet been confirmed. Most CASA measures depend upon concentration, sample volume, type of extender, duration of analysis and thawing temperature. For each attribute, CASA software should provide outputs based on a range rather than means or medians for transformed data. The current review describes development, validation requirements, limitations and future expansions associated with CASA technology.